Awareness Regarding Stroke among Patients with Hypertension Attending a Tertiary Hospital - Ghimire, Dikshya; Acharya, Devaka Kumari (Journal of Nursing Education of Nepal, 2024)
Introduction: Stroke is a global burden especially in developing countries with hypertension being one of the preventable key risk factors. Patients’ awareness of stroke is crucial for its prevention and early and effective management. The objective of this study was to find out the awareness of stroke among patients with hypertension in a tertiary hospital in Nepal. Methods: A descriptive cross-sectional study was conducted in the Outpatient Department of Manmohan Cardiothoracic Vascular and Transplant Centre, Kathmandu. A total of 106 patients diagnosed with hypertension were selected using a non-probability convenience sampling technique. Data was collected from April to May 2024 with face-to-face interviews using a researcher-developed semi-structured interview questionnaire. Data were analyzed with Statistical Package for Social Science version 16 with descriptive statistics for frequency, mean, percentage, and standard deviation and inferential statistics Chi-square and Fischer exact test to measure the association between stroke awareness and selected variables. Results: The study findings revealed that out of 106 hypertensive patients, 40.6% had a good level, 49.1% had a fair level, and 9.4% had a poor level of awareness of stroke. The level of awareness was statistically significant with place of residence, educational status, regular medicine intake, and regular follow-up schedule. Conclusion: This study concludes that patients with hypertension have a fair level of awareness of stroke. Thus, stroke awareness programs incorporating lifestyle modifications, blood pressure control, regular medications, and follow-ups should be conducted to control hypertension and decrease the stroke burden among patients with hypertension.